Electrically conductive carbon‐based (bio)‐nanomaterials for cardiac tissue engineering - Negin Jalilinejad; Mohammad Rabiee; Nafiseh Baheiraei; Ramin Ghahremanzadeh; Reza Salarian; Navid Rabiee; Omid Akhavan; Payam Zarrintaj; Aleksander Hejna; Mohammad Reza Saeb; Ali Zarrabi; Esmaeel Sharifi; et al. (Wiley, 2023)
Abstract A proper self‐regenerating capability is lacking in human cardiac tissue which along with the alarming rate of deaths associated with cardiovascular disorders makes tissue engineering critical. Novel approaches are now being investigated in order to speedily overcome the challenges in this path. Tissue engineering has been revolutionized by the advent of nanomaterials, and later by the application of carbon‐based nanomaterials because of their exceptional variable functionality, conductivity, and mechanical properties. Electrically conductive biomaterials used as cell bearers provide the tissue with an appropriate microenvironment for the specific seeded cells as substrates for the sake of protecting cells in biological media against attacking mechanisms. Nevertheless, their advantages and shortcoming in view of cellular behavior, toxicity, and targeted delivery depend on the tissue in which they are implanted or being used as a scaffold. This review seeks to address, summarize, classify, conceptualize, and discuss the use of carbon‐based nanoparticles in cardiac tissue engineering emphasizing their conductivity. We considered electrical conductivity as a key affecting the regeneration of cells. Correspondingly, we reviewed conductive polymers used in tissue engineering and specifically in cardiac repair as key biomaterials with high efficiency. We comprehensively classified and discussed the advantages of using conductive biomaterials in cardiac tissue engineering. An overall review of the open literature on electroactive substrates including carbon‐based biomaterials over the last decade was provided, tabulated, and thoroughly discussed. The most commonly used conductive substrates comprising graphene, graphene oxide, carbon nanotubes, and carbon nanofibers in cardiac repair were studied.